Searching for the Secret of Stickiness: How Biofilms Adhere to Surfaces - Jiang, Zhaowei; Nero, Thomas; Mukherjee, Sampriti; Olson, Rich; Yan, Jing (Frontiers in Microbiology, 2021)
Bacterial biofilms are communities of cells enclosed in an extracellular polymeric matrix (EPS) in which cells adhere to each other and to foreign surfaces. The development of a biofilm is a dynamic process that involves multiple steps including cell-surface attachment, matrix production, and population expansion. Increasing evidence indicates that biofilm adhesion is one of the main factors contributing to biofilm-associated infections in clinics and biofouling in industrial settings. This review focuses on describing biofilm adhesion strategies among different bacteria, including Vibrio cholerae, Pseudomonas aeruginosa, and Staphylococcus aureus. Techniques to characterize biofilm adhesion are also reviewed. The understanding of biofilm adhesion strategies can guide the development of novel approaches to inhibit or manipulate biofilm adhesion and growth.